Socio-Economic Impacts of Wildlife Tourism in Kasara, Chitwan - Puri, Janak (Journal of APF Command and Staff College, 2019)
Tourism is considered as one of the largest and fastest developing sectors of the world. Its high growth and development rates bring considerable volumes of foreign currency inflows, infrastructure development, employment generation, regional development, economic multiplier effects and introduction between host and guest peoples experience actively affect various sectors of society, which can positively affected to the social and economic development. However the tourism also generates a number of other negative socio-economic impacts on local communities. This study considers the mainly socio-economic impacts on local community trough tourism development in Kasara. The study is focused to identify the social and economic impacts on local community and their perception towards the tourism. The study is adapted the qualitative methodology and the data is generated through primary and secondary source, personal interviews, discussions and social interaction. The study identified that community has developed positive attitudes about the tourism development and the community is accepted tourism as a major income source through active and passive participations. As usually the tourism has generated both positive and negative impacts in the society. However, the negative impacts are at a minimum level when compare with the positive impacts. The social tradition, culture and human behaviour exchange between host guest interactions. The tourism revitalizes the culture and sometime declines the culture of the host country. The tourism helps to develop the livelihood of the people and can earn money from the different business and cultural activities. Community empowerment and their capacity building are highly important in this context.